Miracle Le`Company / Mohd Khairul Sam Muadin... [et al.] - Jainudin, Siti Norzaineh; John, Jennifer; Mahat, Wenddy; Sakai, Dora; Muadin, Mohd Khairul Sam (2014)
Nowadays, the cases of obesity among people around the world is increasing not exception our country, Malaysia. Our Health Ministry was implement a great effort to held a lot of health campaigns in order to reduce the obesity rates. Regarding to this matter, Miracle Le' Company (MLC) was created to become catalyst to overcome this problem. Hence, this company took that solution as their golden opportunity to venture in health services orientation. We are absolutely concerned about people life style. Due to that reason, we came forward by providing people with 3 in 1 complete services. What are 3 in 1 complete services stand for? It is about the three phases that we implement into our business and it is must go through by the customer according to the package that requested. Phase 1: Health and Care Consultation. This is the first phase that will exainine your health and physical condition. Your height and weight will be measure by a high quality of health measurement in purpose to get know whether your BMI is balance or not. This phase will determine what your next treatment is. Phase 2: Fitness training. We provide customer with two different types of fitness, which is modern method and contemporary method. Modem method is conducted by using gymnasium equipment. Whereby contemporary method is consist of yoga and zumba session. Based on your health historical data, we can identify which session is suit for you. Phase 3: Fashion and personality consultation. This is the last phase that must be complete with. There is skilful trainer that will give you a lesson on how to recognize yourself internally and externally. This is important to bring yourself out confidently with a new look. Every people have a dream to become beautiful no matter it is man or woman. This is the outcome that we concern of.